2023
DOI: 10.3389/fnhum.2023.1256415
|View full text |Cite
|
Sign up to set email alerts
|

A state-of-the-art review of functional magnetic resonance imaging technique integrated with advanced statistical modeling and machine learning for primary headache diagnosis

Ming-Lin Li,
Fei Zhang,
Yi-Yang Chen
et al.

Abstract: Primary headache is a very common and burdensome functional headache worldwide, which can be classified as migraine, tension-type headache (TTH), trigeminal autonomic cephalalgia (TAC), and other primary headaches. Managing and treating these different categories require distinct approaches, and accurate diagnosis is crucial. Functional magnetic resonance imaging (fMRI) has become a research hotspot to explore primary headache. By examining the interrelationships between activated brain regions and improving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 147 publications
(172 reference statements)
0
1
0
Order By: Relevance
“…In addition, key areas of migraine research include further exploration of molecular markers and the use of imaging techniques to identify key mechanisms and triggers. In a longitudinal neuroimaging study, the duration of the aura phase of a spontaneous human migraine attack was found to be 48 h using MRI, and hypothalamic activation may serve as a potential marker for this staging ( 75 , 81 ). In summary, the potential of CAT in migraine treatment is remarkable, offering a range of pharmacological and non-pharmacological options that can be tailored to the therapeutic needs of individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, key areas of migraine research include further exploration of molecular markers and the use of imaging techniques to identify key mechanisms and triggers. In a longitudinal neuroimaging study, the duration of the aura phase of a spontaneous human migraine attack was found to be 48 h using MRI, and hypothalamic activation may serve as a potential marker for this staging ( 75 , 81 ). In summary, the potential of CAT in migraine treatment is remarkable, offering a range of pharmacological and non-pharmacological options that can be tailored to the therapeutic needs of individual patients.…”
Section: Discussionmentioning
confidence: 99%